PENDEKATAN CLTS (COMMUNITY LEAD TOTAL SANITATION) UNTUK MENGUBAH PERILAKU KESEHATAN PADA MASYARAKAT DESA KENONGO KECAMATAN GUCIALIT KABUPATEN LUMAJANG - Husni Abdul Gani; Didit Sulistyanto (Fakultas Kesehatan Masyarakat, Universitas Jember, 2011)
This article describes the implementation of CLTS (Community Lead Total Sanitation) are applied to change the unhealthy defecation behavior in the community of Kenongo village Sub Gucialit Lumajang successful in a short time. In general, the success of this program due to full community involvement in the form of awareness of the need for healthy living. Uniting perception program objectives and interests of the community do well through the 5 stages of CLTS triggers. This success is also supported by the real condition of the community of Kenongo village who already has material and immaterial capital in the form of local cultural values so that local capital could act as predeposisi, enabling and reinforcing. Key words : innovation, healthy behaviors, CLTS approach